The empirics of trade and growth: Where are the policy recommendations? - Klaus Wälde; Christina Wood (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2000)
Existing literature repeatedly documented a strong correlation between trade and growth. It has also shown a causal effect of imports (though not necessarily exports) on growth in simultaneous equation models but to a lesser extent in Granger-causality tests. Export and import taxes have sometimes been found to negatively affect growth. Drawing policy conclusions from these general findings for a particular country is difficult not only because of the contradictory results but also because of potential second best world effects and the implied endogeneity of trade policy. Policy recommendations for a specific country require a careful analysis of market and institutional arrangements and can not be based on the existing cross-country literature.
Keywords: 330; Außenwirtschaft; Wirtschaftswachstum; Neue Wachstumstheorie; Exportinduziertes Wachstum; Außenhandelspolitik; Freihandel; Theorie; Welt